Infection of Grapevines by Some Fungi Associated with Esca. I. «Fomitiporia punctata» as a Wood-Rot Inducer - Graniti, Antonio; Giovanni, Bruno; Ciccarone, Claudio; Sparapano, Lorenzo (Phytopathologia Mediterranea, 2000)
Inoculation experiments with three strains of Fomitiporia punctata on grapevine cv. Sangiovese and on grafted ‘Italia’ rootstocks were carried out in southern Italy in 1992-1993. Inoculations were performed on fresh wounds made on the spurs, branches and trunks of vines showing no symptoms of esca. The fungus developed in the discoloured wood around the inoculation site, and caused white rot within two years. No symptoms were induced on foliage or fruit of the infected vines, nor was there any significant difference in virulence of the strains of F. punctata. After 2 years, re-isolation of F. punctata from the diseased woody tissues was successful, whereas no other species of fungi suspected to act as a “precursor” of wood decay were isolated. In 1999, further experiments were carried out with one strain of F. punctata on standing vines cv. Italia and Matilde free of any sign of wood deterioration. The development of internal symptoms was recorded monthly. The results indicated that the cv. Matilde was less susceptible than the cv. Italia. The first signs of spongy wood decay appeared 6 months after inoculation on both cultivars. F. punctata was re-isolated from the infected vines, whereas no species of Phaeoacremonium or other wood-decaying fungi were isolated from either inoculated or non-inoculated vines. These findings suggest that F. punctata behaves as a primary pathogen, being able to cause wood deterioration and spongy decay both on adult and young grapevines in a relatively short time, without the prior or concurrent action of other fungi.